Odyssey Self Reflection - Flower bouquet / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif
The beauty of flowers bouquet had motivated me to produce artworks about flowers. My artwork applied the element of flowers repetition, warm and cool colour. Wood and plastic spoon was the main material to make the sculpture. In printmaking, I used mixed techniques which are linocut and stencil.